Net illumination is more effective for reducing fisheries bycatch at night - Kayla M. Burgher; Kyli E. Denton; John Wang; S. Hoyt Peckham; Daniel Aguilar-Ramirez; Jesse F. Senko (Reviews in Fish Biology and Fisheries, 2026)

Weaving Indigenous and Western knowledge systems across a continuum of knowledge and decision-making spaces - Natalie C Ban; Hannah V Watkins; Robyn E Forrest; Alejandro Frid; Carrie A Holt; Sierra J Hall; Christina N Service; Luisa Ramirez; Daniel L Curtis; Kyle L Wilson; Lawrence Ignace; Andrea J Reid; et al. (Current Opinion in Environmental Sustainability, 2026)

Supplementation of a DHA commercial lipid emulsion in diets for tropical gar (Atractosteus tropicus) larvae: effects on growth, cannibalistic behavior, digestive enzyme activity, and aggressiveness-related genes - César Antonio Sepúlveda-Quiroz; Carina Shianya Alvarez-Villagomez; Luis Daniel Jiménez-Martínez; Emyr Saul Peña-Marín; Omar Mendoza-Porras; Graciela María Pérez-Jiménez; Gloria Gertrudys Ascencio-Alcudia; Fernando Barreto-Curiel; Mario A. Galaviz-Espinoza; Dariel Tovar-Ramirez; Rafael Martínez-García; Carlos Alfonso Álvarez-González (Fish Physiology and Biochemistry, 2026)

Predictors of worsening food security among women living with and without HIV and seronegative women during COVID-19: a mixed methods study - Jenni M. Wise; Hilary Bethancourt; Torsten B. Neilands; Anna Leddy; Gypsyamber D’Souza; Mirjam-Colette Kempf; Janet M. Turan; Gina Wingood; M. Reuel Friedman; Jennafer Kwait; Lakshmi Goparaju; Mardge Cohen; et al. (Food Security, 2026)
This study aimed to assess the prevalence, severity, predictors, and lived experiences of food insecurity among women enrolled in the Women’s Interagency HIV Study in the USA in 2020, at the height of the COVID-19 pandemic. We hypothesized that pre-existing socioeconomic and health-related disparities would heighten the risk of worsening food insecurity during the pandemic. The 10-item US Household Food Security Survey was administered to participants three times between June and September 2020. Multilevel mixed-effects ordered logistic regression models were used to estimate the odds of worsening food security compared to pre-pandemic baseline data. Qualitative interviews were conducted among a subset of participants to add understanding of the lived experience of food insecurity during the pandemic, beyond what quantitative measures could provide. Among 1,506 women, 28% had marginal to very low food security at baseline, and between 13.6-17.3% experienced worsening food security during pandemic measures. Women with household incomes <$12,000/year were particularly vulnerable to worsening food insecurity, including those experiencing unemployment (OR: 2.06, 95% CI:1.36, 3.13), job loss (OR: 1.47, 95% CI: 1.04-2.06), loss of financial support (OR: 1.91,95% CI: 1.23, 2.97), and those with reduced access to usual sources of food (OR: 7.67, 95% CI:4.78, 12.30). While the quantitative data suggest that relatively few women experienced worsening food security during the pandemic, the qualitative data suggest that many more women had difficulty accessing preferred and healthy foods and experienced disruption to social services, which typically facilitate the ability to access food. Women described how informal social systems (e.g., neighborhood gardens, sharing resources) bridged the gap left by more formal systems during this time. Taken together, these findings suggest that women with pre-existing socioeconomic vulnerability were disproportionately and negatively impacted by the social and economic disruptions of the COVID-19 pandemic. Interventions are needed to address structural vulnerabilities, improve safeguards to food security during times of distress, and harness the capacity of community-based support systems.

IoT-enabled air quality prediction using ensemble machine learning: a case study in San Salvador, El Salvador - Josue Ramirez-Ramirez; Daniel Amaya-Cruz; Griselda Zepeda-Navarro; Bayron Carpio-Villaran; Miguel Alfaro-Vides; Yakdiel Rodriguez-Gallo; Omar Otoniel Flores-Cortez; Carlos Osmín Pocasangre Jiménez; Werner David Meléndez (Air Quality, Atmosphere & Health, 2026)

Elevated levels of circulating plasma sPDGFRβ in cognitively impaired APOE4 carriers - Abhay P. Sagare; Trevor Lohman; Ivan Ramirez; Elizabeth B. Joe; Michael G. Harrington; Helena C. Chui; Lon S. Schneider; Hussein N. Yassine; John M. Ringman; Arthur W. Toga; Daniel A. Nation; Berislav V. Zlokovic (GeroScience, 2026)
Increased levels of cerebrospinal fluid (CSF) soluble platelet-derived growth factor receptor-β (sPDGFRβ), a marker of blood–brain barrier (BBB)-associated pericyte cell injury, have been shown to correlate with increased BBB permeability and severity of Alzheimer’s disease (AD) pathology. It has been also shown that increased CSF sPDGFRβ levels can predict cognitive dysfunction in APOE4 carriers bearing the main susceptibility gene for AD. Whether plasma sPDGFRβ levels are also elevated in APOE4 carriers has not been explored. Here, we analyzed plasma samples for sPDGFRβ levels, Ab 42/40 ratio, and pTau217 in 115 APOE3 homozygotes and APOE4 carriers with Clinical Dementia Rating (CDR) score of 0 and 0.5. Our data show that plasma sPDGFRβ levels are increased in APOE4 carriers with cognitive impairment compared to APOE4 carriers that are cognitively unimpaired as well as relative to cognitively impaired APOE3 carriers even after controlling for plasma Aβ 42/40 ratio and pTau217. Thus, our data suggest that plasma sPDGFRβ is a useful biomarker of brain pericytes/BBB damage in APOE4 carriers.

Strategic assessment of socio-environmental conflicts in solar hydrogen production: a case of Antofagasta, Chile - Isidora Abasolo Farfan; Alejandro Fernández Gil; René Garrido Lazo; Carolina Bonacic Castro; Pablo Rodríguez Machuca; Daniel Serafini; Roberto Carmona Campos; Angel Rodríguez Soto; Marcelo Mena-Carrasco Soto; Luis Ramirez Camargo; Javier Valdes; Yunesky Masip Macia (Clean Technologies and Environmental Policy, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Diesel particulate matter health impacts in California: Trends, source apportionment, and policy implications - Shuming Du; Pingkuan Di; XueMeng Chen; Yiting Li; Yunle Chen; Karry Liu; Zhen Liu; Abdullah Mahmud; Melissa Venecek; Daniel Chau; Wenli Yang; Roger Kwok; et al. (Environmental Pollution, 2025)

How Do Patient Outcomes in Mechanical Thrombectomy for Large-Core Stroke Vary Based on Neuroimaging Modalities Used for Patient Selection? A Multicenter Multinational Study - Omar Alwakaa; Rahim Abo Kasem; Felipe Ramirez-Velandia; Aryan Wadhwa; Kimberly Han; Michael R. Levitt; Ali Alaraj; Pascal Jabbour; Joon-Tae Kim; Brian Howard; Ali Alawieh; Stacey Quintero Wolfe; et al. (Translational Stroke Research, 2025)

HydroServer: A software stack supporting collection, communication, storage, management, and sharing of data from in situ environmental sensors - Jeffery S. Horsburgh; Kenneth Lippold; Daniel L. Slaugh; Maurier Ramirez (Environmental Modelling & Software, 2025)

Toxicity of six representative polycyclic aromatic compounds in five marine test species - Benjamin P. de Jourdan; David L. Daniel; Piero R. Gardinali; Cesar Ramirez; Chris J. Langdon; Emily Stefansson; Thomas F. Parkerton; William A. Stubblefield (Science of The Total Environment, 2025)

Neuropsychological and Anatomical-Functional Effects of Transcranial Magnetic Stimulation in Post-Stroke Patients with Cognitive Impairment and Aphasia: A Systematic Review - Ignacio Pezoa–Peña; Teresa Julio–Ramos; Igor Cigarroa; Diana Martella; Daniel Solomons; David Toloza–Ramirez (Neuropsychology Review, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Insomnia accelerates the epigenetic clocks in older adults - Nadia Alejandra Rivero-Segura; Julian Daniel Rodriguez Cuartas; Paola Garcia-delaTorre; Sergio Sanchez-Garcia; Ricardo Ramirez-Aldana; Juan Carlos Gomez-Verjan (GeroScience, 2025)

Embryotoxicity of statins and other prescribed drugs with reported off-target effects on cholesterol biosynthesis - Taryn Hartley; Hagir Abdelmagid; Zeenat Abdulsalam; Aliyah Mansion; Emily Howe; Daniel Ramirez; Kaylei White; Emmanuel Tadjuidje (Reproductive Toxicology, 2025)

Groundwater storage loss in the central valley analysis using a novel method based on in situ data compared to GRACE-derived data - Michael D. Stevens; Saul G. Ramirez; Eva-Marie H. Martin; Norman L. Jones; Gustavious P. Williams; Kyra H. Adams; Daniel P. Ames; Sarva T. Pulla (Environmental Modelling & Software, 2025)

Dose-related effects of eugenol: Exploring renal functionality and morphology in healthy Wistar rats - Renner Philipe Rodrigues Carvalho; Rosiany Vieira da Costa; Isadora Ribeiro de Carvalho; Arabela Guedes Azevedo Viana; Camilo Ramirez Lopez; Mariana Souza Oliveira; Luiz Otavio Guimarães-Ervilha; Wassali Valadares de Sousa; Daniel Silva Sena Bastos; Edgar Diaz Miranda; Fábio César Sousa Nogueira; Mariana Machado-Neves (Food and Chemical Toxicology, 2025)

Assessment of geomorphological, hydrometeorological and geological trigger conditions of debris flows in northern Patagonia Andes - Gonzalo Maragaño-Carmona; Ivo Fustos-Toribio; Pablo Moreno-Yaeger; Elisa Ramirez; Daniel Basualto; Wen Nie; Pierre-Yves Descote; Luis F. Robledo (Bulletin of Engineering Geology and the Environment, 2025)

Recurrent Extreme Climatic Events Are Driving Gorgonian Populations to Local Extinction: Low Adaptive Potential to Marine Heatwaves - Sandra Ramirez‐Calero; Daniel Gómez‐Gras; Aldo Barreiro; Nathaniel Bensoussan; Laura Figuerola‐Ferrando; Marc Jou; Àngel López‐Sanz; Paula López‐Sendino; Alba Medrano; Ignasi Montero‐Serra; Marta Pagès‐Escolà; Cristina Linares; et al. (Global Change Biology, 2024)
Extreme climatic events (ECEs), such as marine heatwaves (MHWs), are a major threat to biodiversity. Understanding the variability in ecological responses to recurrent ECEs within species and underlying drivers arise as a key issue owing to their implications for conservation and population recovery. Yet, our knowledge on such ecological responses is limited since it has been frequently gathered following “single‐event approaches” focused on one particular event. These approaches provide snapshots of ecological responses but fall short of capturing heterogeneity patterns that may occur among recurrent ECEs, questioning current predictions regarding biodiversity trends. Here, we adopt a “multiple events” perspective to characterize the effects of recurrent ECEs on the ecological responses in Paramuricea clavata , a Mediterranean temperate coral threatened by MHWs. Through a common‐garden experiment repeated three consecutive years with the same individuals from three populations, we assessed the respective roles of environmental (year effect), genetic (population effect), and phenotypic (population‐by‐environment interactions effect) components in the ecological response to recurrent heat stress. The environmental component (year) was the main driver underlying the responses of P . clavata colonies across experiments. To build on this result, we showed that: (i) the ecological responses were not related to population (genetic isolation) and individual (multilocus heterozygosity) genetic make‐up, (ii) while all the individuals were characterized by a high environmental sensitivity (genotype‐by‐environment interactions) likely driven by in situ summer thermal regime. We confront our experimental results to in situ monitoring of the same individuals conducted in 2022 following two MHWs (2018, 2022). This confirms that the targeted populations harbor limited adaptive and plastic capacities to on‐going recurrent ECEs and that P . clavata might face unavoidable population collapses in shallow Mediterranean waters. Overall, we underscore the need to consider the recurrence of ECEs to assess threats to biodiversity and to forecast its evolution.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

A Critical Review of Short Antimicrobial Peptides from Scorpion Venoms, Their Physicochemical Attributes, and Potential for the Development of New Drugs - Pedro Alejandro Fong-Coronado; Verónica Ramirez; Verónica Quintero-Hernández; Daniel Balleza (The Journal of Membrane Biology, 2024)
Scorpion venoms have proven to be excellent sources of antimicrobial agents. However, although many of them have been functionally characterized, they remain underutilized as pharmacological agents, despite their evident therapeutic potential. In this review, we discuss the physicochemical properties of short scorpion venom antimicrobial peptides (ssAMPs). Being generally short (13–25 aa) and amidated, their proven antimicrobial activity is generally explained by parameters such as their net charge, the hydrophobic moment, or the degree of helicity. However, for a complete understanding of their biological activities, also considering the properties of the target membranes is of great relevance. Here, with an extensive analysis of the physicochemical, structural, and thermodynamic parameters associated with these biomolecules, we propose a theoretical framework for the rational design of new antimicrobial drugs. Through a comparison of these physicochemical properties with the bioactivity of ssAMPs in pathogenic bacteria such as Staphylococcus aureus or Acinetobacter baumannii , it is evident that in addition to the net charge, the hydrophobic moment, electrostatic energy, or intrinsic flexibility are determining parameters to understand their performance. Although the correlation between these parameters is very complex, the consensus of our analysis suggests that there is a delicate balance between them and that modifying one affects the rest. Understanding the contribution of lipid composition to their bioactivities is also underestimated, which suggests that for each peptide, there is a physiological context to consider for the rational design of new drugs. Graphical Abstract

Decision-making in open carpooling programs: Perspectives of drivers versus passengers - Willis Simancas; Cristian Vinasco; Daniel Rosas-Satizábal; Hernan Alberto Ortiz-Ramirez; Alvaro Rodriguez-Valencia (Travel Behaviour and Society, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Environmental-related applications of ZnO nanopowders: Photocatalytic activity and photoluminescence response to ethanol - Oscar Marin-Ramirez; Matias Cornet; Daniel Pais Ospina; Milton Manotas-Albor; Mario Millan; Edgar Mosquera-Vargas; Mónica Tirado; David Comedi (Environmental Nanotechnology, Monitoring & Management, 2024)

Associations between urban greenspace and depressive symptoms in Mexico's cities using different greenspace metrics - Maryia Bakhtsiyarava; Yang Ju; Mika Moran; Daniel A. Rodríguez; Iryna Dronova; Xavier Delclòs-Alió; Kari Moore; Marianela Castillo-Riquelme; Cecilia Anza-Ramirez (Applied Geography, 2024)

Tryptophan Reduces Intracohort Cannibalism Behavior in Tropical Gar (Atractosteus tropicus) Larvae - César Antonio Sepúlveda-Quiroz; Graciela María Pérez-Jiménez; Gloria Gertrudis Asencio-Alcudia; Omar Mendoza-Porras; Luis Daniel Jiménez-Martínez; Mario A. Galaviz-Espinoza; Dariel Tovar-Ramirez; Rafael Martinez-Garcia; Carina Shianya Alvarez-Villagomez; Carlos Alfonso Alvarez-Gonzalez (Fishes, 2024)
The intracohort cannibalism present in tropical gar larvae (A. tropicus) generates great problems in its culture, as in other fish species around the world. The addition of tryptophan (Trp) (10, 20, and 30 g/kg) and a control diet (CD) without Trp were evaluated in A. tropicus larvae regarding growth, survival, cannibalism, behavior, digestive enzymatic activity, and genes related to aggressiveness and/or cannibalism in two stages: 0–13 days after hatching (DAH); and only cannibals (14–24 DAH). In the first stage, no differences were observed in growth parameters; cannibalism was lower with the use of Trp, with the lowest percentage being the 10 g/kg Trp treatment (56.75 ± 2.47%) compared to CD (64.75 ± 1.76%). In the second stage, survival was greater in 10 g/kg Trp (75.00 ± 7.07%) than in CD (23.33 ± 5.77%). Thus, cannibalism was lower with 10 g/kg Trp (20.0 ± 10.0%) compared to CD (76.66 ± 5.77%). Cannibal larvae fed with 10 g/kg Trp had a greater enzymatic activity in acid and alkaline proteases and leucine aminopeptidase, as well as the overexpression of avpi1, crh, and htr1a and the subexpression of tph1, th, sstr1, and hdc (p

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Ketorolac removal through photoelectrocatalysis using TiO2 nanotubes in water system - Sebastián Oyarzabal Rodríguez; Luis Erick Coy-Aceves; Jesus Eduardo Daniel Morales; Jose Luis Sanchez-Salas; Carlos Alberto Martínez-Huitle; Milena Maria Ramirez-Rodrigues; Monica Cerro-Lopez (Environmental Science and Pollution Research, 2023)

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Towerpy: An open-source toolbox for processing polarimetric weather radar data - Daniel Sanchez-Rivas; Miguel Angel Rico-Ramirez (Environmental Modelling & Software, 2023)

Circulating Plasma miRNA Homologs in Mice and Humans Reflect Familial Cerebral Cavernous Malformation Disease - Sharbel G. Romanos; Abhinav Srinath; Ying Li; Bingqing Xie; Chang Chen; Yan Li; Thomas Moore; Dehua Bi; Je Yeong Sone; Rhonda Lightle; Nick Hobson; Dongdong Zhang; et al. (Translational Stroke Research, 2023)

Heat stress promotes adaptive physiological responses and alters mrna expression of ruminal epithelium markers in Bos taurus indicus cattle fed low- or high-energy diets - Javier A.M. Meneses; Olavo A.A.L. de Sá; German D. Ramirez-Zamudio; Karolina B. Nascimento; Tathyane R.S. Gionbelli; Matheus H. Luz; Márcio M. Ladeira; Daniel R. Casagrande; Mateus P. Gionbelli (Journal of Thermal Biology, 2023)

Belize Blue Carbon: Establishing a national carbon stock estimate for mangrove ecosystems - Hannah K. Morrissette; Stacy K. Baez; Lisa Beers; Nadia Bood; Ninon D. Martinez; Kevin Novelo; Gilbert Andrews; Luis Balan; C. Scott Beers; Sumeet A. Betancourt; Reynel Blanco; Eeryn Bowden; et al. (Science of The Total Environment, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Health and equity impacts from electrifying drayage trucks - Monica Ramirez-Ibarra; Jean-Daniel M. Saphores (Transportation Research Part D: Transport and Environment, 2023)

Petrological, petrophysical and petrothermal study of a folded sedimentary succession: the Oliana anticline (Southern Pyrenees), outcrop analogue of a geothermal reservoir - Pedro Ramirez-Perez; Irene Cantarero; Gabriel Cofrade; Daniel Muñoz-López; David Cruset; Jean-Pierre Sizun; Anna Travé (Global and Planetary Change, 2023)

Economic analysis of the benefits to petroleum refiners for low carbon boosted spark ignition biofuels - Nicholas A. Carlson; Avantika Singh; Michael S. Talmadge; Yuan Jiang; George G. Zaimes; Shuyun Li; Troy R. Hawkins; Lauren Sittler; Aaron Brooker; Daniel J. Gaspar; Robert L. McCormick; M.M. Ramirez-Corredores (Fuel, 2023)

Economic and environmental analysis to evaluate the potential value of co-optima diesel bioblendstocks to petroleum refiners - Yuan Jiang; George G. Zaimes; Shuyun Li; Troy R. Hawkins; Avantika Singh; Nicholas Carlson; Michael Talmadge; Daniel J. Gaspar; M.M. Ramirez-Corredores; Andrew W. Beck; Ben Young; Lauren Sittler; et al. (Fuel, 2023)

Effects of landscape characteristics, anthropogenic factors, and seasonality on water quality in Portland, Oregon - Katherine Gelsey; Heejun Chang; Daniel Ramirez (Environmental Monitoring and Assessment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Commentary: Face masks in physical education classes during the COVID-19 delta variant wave: a call for awareness - Andrew Sortwell; Rodrigo Ramirez-Campillo; Jorge Knijnik; Pedro Forte; Daniel Marinho; Ricardo Ferraz; Kevin Trimble (German Journal of Exercise and Sport Research, 2022)

The Cerebellar Gene Database: a Collective Database of Genes Critical for Cerebellar Development - Miguel Ramirez; Joshua Wu; Matthew Liu; Derek Wu; Dave Weeden; Daniel Goldowitz (The Cerebellum, 2022)
This report presents the first comprehensive database that specifically compiles genes critical for cerebellar development and function. The Cerebellar Gene Database details genes that, when perturbed in mouse models, result in a cerebellar phenotype according to available data from both Mouse Genome Informatics and PubMed, as well as references to the corresponding studies for further examination. This database also offers a compilation of human genetic disorders with a cerebellar phenotype and their associated gene information from the Online Mendelian Inheritance in Man (OMIM) database. By comparing and contrasting the mouse and human datasets, we observe that only a small proportion of human mutant genes with a cerebellar phenotype have been studied in mouse knockout models. Given the highly conserved nature between mouse and human genomes, this surprising finding highlights how mouse genetic models can be more frequently employed to elucidate human disease etiology. On the other hand, many mouse genes identified in the present study that are known to lead to a cerebellar phenotype when perturbed have not yet been found to be pathogenic in the cerebellum of humans. This database furthers our understanding of human cerebellar disorders with yet-to-be-identified genetic causes. It is our hope that this gene database will serve as an invaluable tool for gathering background information, generating hypotheses, and facilitating translational research endeavors. Moreover, we encourage continual inputs from the research community in making this compilation a living database, one that remains up-to-date with the advances in cerebellar research.

Invasive Chinook Salmon in Chile: Stakeholder Perceptions and Management Conflicts around a New Common-use Resource - Beatriz Cid-Aguayo; Alejandro Ramirez; Maritza Sepúlveda; Daniel Gomez-Uchida (Environmental Management, 2021)

The conservation status of the world’s freshwater molluscs - Monika Böhm; Nadia I. Dewhurst-Richman; Mary Seddon; Sophie E. H. Ledger; Christian Albrecht; David Allen; Arthur E. Bogan; Jay Cordeiro; Kevin S. Cummings; Annabelle Cuttelod; Gustavo Darrigran; Will Darwall; et al. (Hydrobiologia, 2021)

Corrigendum: Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)

Marine Genetic Resources in Areas Beyond National Jurisdiction: Promoting Marine Scientific Research and Enabling Equitable Benefit Sharing - Alex D. Rogers; Amy Baco; Elva Escobar-Briones; Duncan Currie; Kristina Gjerde; Judith Gobin; Marcel Jaspars; Lisa Levin; Katrin Linse; Muriel Rabone; Eva Ramirez-Llodra; Javier Sellanes; et al. (Frontiers in Marine Science, 2021)
Growing human activity in areas beyond national jurisdiction (ABNJ) is driving increasing impacts on the biodiversity of this vast area of the ocean. As a result, the United Nations General Assembly committed to convening a series of intergovernmental conferences (IGCs) to develop an international legally-binding instrument (ILBI) for the conservation and sustainable use of marine biological diversity of ABNJ [the biodiversity beyond national jurisdiction (BBNJ) agreement] under the United Nations Convention on the Law of the Sea. The BBNJ agreement includes consideration of marine genetic resources (MGR) in ABNJ, including how to share benefits and promote marine scientific research whilst building capacity of developing states in science and technology. Three IGCs have been completed to date with the fourth delayed by the Covid pandemic. This delay has allowed a series of informal dialogues to take place between state parties, which have highlighted a number of areas related to MGR and benefit sharing that require technical guidance from ocean experts. These include: guiding principles on the access and use of MGR from ABNJ; the sharing of knowledge arising from research on MGR in ABNJ; and capacity building and technology transfer for developing states. In this paper, we explain what MGR are, the methods required to collect, study and archive them, including data arising from scientific investigation. We also explore the practical requirements of access by developing countries to scientific cruises, including the sharing of data, as well as participation in research and development on shore whilst promoting rather than hindering marine scientific research. We outline existing infrastructure and shared resources that facilitate access, research, development, and benefit sharing of MGR from ABNJ; and discuss existing gaps. We examine international capacity development and technology transfer schemes that might facilitate or complement non-monetary benefit sharing activities. We end the paper by highlighting what the ILBI can achieve in terms of access, utilization, and benefit sharing of MGR and how we might future-proof the BBNJ Agreement with respect to developments in science and technology.

Phosphorus Solubilizing and Mineralizing Bacillus spp. Contribute to Rice Growth Promotion Using Soil Amended with Rice Straw - Luis F. Gomez-Ramirez; Daniel Uribe-Velez (Current Microbiology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Performance of precipitation products obtained from combinations of satellite and surface observations - José Roberto Rozante; Enver Ramirez Gutierrez; Alex de Almeida Fernandes; Daniel A. Vila (International Journal of Remote Sensing, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Differential Expression of Striatal ΔFosB mRNA and FosB mRNA After Different Levodopa Treatment Regimens in a Rat Model of Parkinson’s Disease - Victoria Palafox-Sanchez; Victoria Sosti; Gabriel Ramirez-García; Jaime Kulisevsky; José Aguilera; I. Daniel Limón (Neurotoxicity Research, 2019)

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

The National Cancer Institute R25 Cancer Education Grants Program: A Workshop Report - Jeannette F. Korczak; Davyd W. Chung; Erica Rosemond; Daniel D. Von Hoff; Richard L. Haspel; John W. Waterbor; Shine Chang; Amelie G. Ramirez; Susan Perkins; Jonathan Wiest; Ming Lei (Journal of Cancer Education, 2017)

Association of KIR3DL1/S1 and HLA-Bw4 with CD4 T cell counts in HIV-infected Mexican mestizos - Daniel Hernández-Ramírez; Mario A. Esparza-Pérez; José L. Ramirez-Garcialuna; J. Rafael Arguello; Peter B. Mandeville; Daniel E. Noyola; Christian A. García-Sepúlveda (Immunogenetics, 2015)

Association of obesity and circulating adipose stromal cells among breast cancer survivors - Sagar Ghosh; Daniel Hughes; Dorothy Long Parma; Amelie Ramirez; Rong Li (Molecular Biology Reports, 2014)

Predictors of regional establishment success and spread of introduced non‐indigenous vertebrates - Craig R. Allen; Kristine T. Nemec; Donald A. Wardwell; Justin D. Hoffman; Mathew Brust; Karie L. Decker; Daniel Fogell; Jennifer Hogue; Aaron Lotz; Thaddeus Miller; Marcy Pummill; Luis E. Ramirez‐Yañez; et al. (Global Ecology and Biogeography, 2013)
Aim To provide the first analysis of predictors of both establishment and spread, both within and across taxa, for all vertebrate taxa within a region. We used F lorida, USA , as our study system because it has a well‐documented history of introduction and invasion, and is a hotspot for biological invasions. Location F lorida, USA. Methods We analysed non‐indigenous species ( NIS ) data from peninsular F lorida – which included both successful and unsuccessful introductions from all vertebrate classes – to determine the best predictors of both establishment and spread for fish (65 species), herpetofauna (63 species), birds (71 species) and mammals (25 species). We used 10 variables proposed to be associated with the establishment and spread of NIS : body mass, geographic origin, reproductive rate, diet generalism, native‐range size, latitude of native range, number of NIS present at date of introduction, presence of NIS congeners, morphological proximity to other NIS (in terms of body mass) and propagule pressure. A multimodel selection process was used with an information‐theoretic approach to determine the best fit models for predicting establishment and spread of NIS . We selected a priori plausible predictive models for establishment and spread. Results Large native‐range size and small body mass best predicted establishment of non‐indigenous herpetofauna. The presence of NIS congeners had the largest positive effect on the establishment of non‐indigenous fish. For mammals, the number of NIS present at the time of introduction best explained establishment. No single model best explained bird establishment. For all taxa but birds, the number of NIS present at time of introduction was included in at least one of the best‐supported models for explaining spread. Main conclusions Our analyses suggest that predictors of establishment and spread differ across vertebrate taxa at the scale studied. Most predictive variables can be interpreted as measures of competitive interactions among species.

Draft whole genome sequence of the cyanide‐degrading bacterium P seudomonas pseudoalcaligenes CECT 5344 - Víctor M. Luque‐Almagro; Felipe Acera; Ma Isabel Igeño; Daniel Wibberg; Ma Dolores Roldán; Lara P. Sáez; Magdalena Hennig; Alberto Quesada; Ma José Huertas; Jochen Blom; Faustino Merchán; Ma Paz Escribano; et al. (Environmental Microbiology, 2013)
Summary P seudomonas pseudoalcaligenes CECT 5344 is a Gram‐negative bacterium able to tolerate cyanide and to use it as the sole nitrogen source. We report here the first draft of the whole genome sequence of a P . pseudoalcaligenes strain that assimilates cyanide. Three aspects are specially emphasized in this manuscript. First, some generalities of the genome are shown and discussed in the context of other P seudomonadaceae genomes, including genome size, G + C content, core genome and singletons among other features. Second, the genome is analysed in the context of cyanide metabolism, describing genes probably involved in cyanide assimilation, like those encoding nitrilases, and genes related to cyanide resistance, like the cio genes encoding the cyanide insensitive oxidases. Finally, the presence of genes probably involved in other processes with a great biotechnological potential like production of bioplastics and biodegradation of pollutants also is discussed.

Optimization of gene delivery methods in Xenopus laevis kidney (A6) and Chinese hamster ovary (CHO) cell lines for heterologous expression of Xenopus inner ear genes - Daniel Ramirez-Gordillo; Casilda Trujillo-Provencio; V. Bleu Knight; Elba E. Serrano (In Vitro Cellular & Developmental Biology - Animal, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

The combined inelastic neutron scattering and solid state DFT study of hydrogen atoms dynamics in a highly ordered kaolinite - Ľubomír Smrčok; Daniel Tunega; Anibal Javier Ramirez-Cuesta; Eva Scholtzová (Physics and Chemistry of Minerals, 2010)

Multisensory processing and oscillatory activity: analyzing non-linear electrophysiological measures in humans and simians - Daniel Senkowski; Manuel Gomez-Ramirez; Peter Lakatos; Glenn R. Wylie; Sophie Molholm; Charles E. Schroeder; John J. Foxe (Experimental Brain Research, 2007)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)